Design and Implementation of a Web-Based Internet Access Monitoring System Using a MikroTik Router - Hendri Alamsyah; Abdussalam Al Akbar (Jurnal Media Computer Science, 2026)
Internet network is a primary need in educational environment especially at SMP Negeri 3 of Lebong Regency of Bengkulu Province. SMP Negeri 3 of Lebong Regency already has internet network using Telkom Indihome provider with 30 Mbps Bandwidth. School does not have a system that can help monitor user internet access, where this can allow better control over user behavior on the network and can ensure that access to the website is in accordance with school policy. The internet access monitoring application is built using PHP programming language with MySQL database. The database is used to store the results of taking user internet access logs and blocked websites. The internet access monitoring application is accessed on the local network by activating the apache web server on the admin laptop and opening a browser to open a web-based application with the localhost/monitoring link. Based on the testing that has been conducted at SMP Negeri 3 of Lebong Regency, the results obtained are that the internet access monitoring application at SMP Negeri 3 of Lebong Regency based on the web can provide information related to users (IP Address) who are active on the internet network and information on sites (IP Address) that have been accessed by each user. In addition, this application can help block websites that are not desired to be accessed by users.